Hybridoperationssaal vs. konventioneller Operationssaal: betriebswirtschaftliche Gegenüberstellung in der Gefäßchirurgie am Beispiel der endovaskulären Aneurysmachirurgie - Attigah, Nicolas; Demirel, Serdar; Hakimi, Maani; Müller, Andreas; Geis, Uwe; Böckler, Dittmar (Der Chirurg, 2017)
BackgroundWith changing treatment modalities in vascular surgery towards incorporating more endovascular solutions, increased numbers of hybrid operating theatres are being introduced to meet the sterility and imaging quality requirements. These cost-intensive acquisitions however have never been evaluated from an economic perspective. In this study we evaluated cost-relevant parameters before and after the introduction of a hybrid operating room using the example of endovascular aneurysm repair (EVAR) performed in patients with abdominal aortic aneurysms (AAA).MethodsRetrospective analysis of prospectively collected data. The 4‑year period before the introduction of a hybrid operating room were compared with the 4‑year period following introduction. Between 2007 and 2010, 97 EVAR procedures were performed before the implementation of a hybrid operating room and 50 EVAR procedures were performed with a hybrid operating room (2012-2015). We evaluated process cost-relevant parameters (operating time) and diagnosis-related group (DRG) parameters (case load, case mix, case mix index).ResultsThe operating time was significantly reduced on average by 23.5 min (120 min [102-140] vs. 96.5 min [90-120]; p < 0.0001) with a hybrid operating room. This led to a reduction in costs of 276.17 EUR for an EVAR procedure. The case load of EVAR increased from 308 cases from 2007-2010 to 380 cases from 2012-2015 . The associated case mix also increased from 1580 to 1986 points. The total number of case mix points of all managed operative interventions in the operating theatre before and after conversion to a hybrid operating room grew significantly by 17.33% from 8420 to 9880 (p < 0.03) in the compared time periods.ConclusionWith detailed, demand-oriented planning, a hybrid operating room can have a favourable economic effect due to a reduction of operating time and the overall lowering of process costs. Thus a refinancing in the long-term is feasible. In addition, this can lead to an increase in the total number and complexity of endovascular procedures.
Mit englischer Zusammenfassung unter dem Titel: Hybrid operating rooms versus conventional operating rooms
Gesehen am 21.08.2018